EP1335 Total laparoscopic Hudson's procedure, pelvic and para-aortic node dissection, omentectomy with primary re-anastomosis and loop ileostomy for endometrioid adenocarcinoma in association with endometriosis. (1st November 2019) - Graham, M; Harley, I; Armstrong, A; Craig, E; Wilson, C
Abstract : Introduction/Background: Video presentation of procedure. Methodology: This video will outline the procedure above. Results: This patient previously underwent a right ovarian cystectomy for endometrioma with final histopathology confirming an endometrioid adenocarcinoma in association with endometriosis - at least FIGO 1C1. Pre-operative MRI and CT suggested endometriosis/disease in recto-uterine pouch, with no evidence of disease outside the pelvis. Completion surgery with a Hudson's and comprehensive surgical staging was planned as a laparoscopic procedure. On initial inspection Intravenous Indocyanine Green (ICG) was used to facilitate the identification of endometriosis/disease in the pelvis. Following surgical staging, including en-bloc dissection of the uterus, tubes, ovaries and rectosigmoid, the specimen was removed via the vagina with the aid of an Alexis retractor. For re-anastamosis the distal descending colon was delivered through the vagina, the anvil applied, and the anastomosis completed laparoscopically. This anastomosis was then de-functioned via a loop ileostomy. ICG was used to confirm perfusion of the anastomosis. Conclusion: In this video we will show the steps of this laparoscopic procedure where bulky disease was resected en-bloc laparoscopically. Disclosure: nil